2003
DOI: 10.1095/biolreprod.103.020651
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin: Roles in Implantation and Placentation1

Abstract: Osteopontin (OPN) is an acidic member of the small integrin-binding ligand N-linked glycoprotein (SIBLING) family of extracellular matrix proteins/cytokines that undergoes extensive posttranslational modification, including phosphorylation, glycosylation, and cleavage, yielding molecular mass variants ranging in size from 25 to 75 kDa. The result is a versatile protein(s) with multiple functions arising from its role as a mediator of cell-cell and cell-extracellular matrix (ECM) communication that encompass bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
258
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(272 citation statements)
references
References 175 publications
9
258
1
4
Order By: Relevance
“…It is a glandular secretory protein that functions during implantation in the extracellular matrix as a mediator of cell-to-cell adhesion and cell migration during trophoblast attachment (Johnson et al 2003). There is much evidence to suggest that SPP1 mRNA expression is regulated by progesterone and does not appear to be influenced by IFNT in the ovine endometrium (see review by Johnson et al 2003).…”
Section: Evaluation Of the Bovine Uterine Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a glandular secretory protein that functions during implantation in the extracellular matrix as a mediator of cell-to-cell adhesion and cell migration during trophoblast attachment (Johnson et al 2003). There is much evidence to suggest that SPP1 mRNA expression is regulated by progesterone and does not appear to be influenced by IFNT in the ovine endometrium (see review by Johnson et al 2003).…”
Section: Evaluation Of the Bovine Uterine Environmentmentioning
confidence: 99%
“…It is a glandular secretory protein that functions during implantation in the extracellular matrix as a mediator of cell-to-cell adhesion and cell migration during trophoblast attachment (Johnson et al 2003). There is much evidence to suggest that SPP1 mRNA expression is regulated by progesterone and does not appear to be influenced by IFNT in the ovine endometrium (see review by Johnson et al 2003). Progesterone control was not indicated in the present study and a recent report suggested that SPP1 was regulated independently of pregnancy, IFNT and progesterone in an ovine cell culture system (Ahn et al 2009).…”
Section: Evaluation Of the Bovine Uterine Environmentmentioning
confidence: 99%
“…They play a dominant role in interactions with ECM to transduce cellular signals in uterine epithelial cells and conceptus trophoblast , Johnson et al 2003a. The central role of integrins in the implantation adhesion cascade is to bind ECM ligand(s) to cause cytoskeletal reorganization, stabilize adhesion, and mediate cell migration, proliferation and differentiation through numerous signaling intermediates (Giancotti & Ruoslahti 1999).…”
Section: Integrinsmentioning
confidence: 99%
“…More recently it has been detected in many tissues and fluids, including urine (Sorenson et al 1995), milk (Sorensen & Petersen 1993, Sorensen et al 2003, kidney (Xie et al 2001), uterine endometrium of rabbits (Apparao et al 2003), sheep (Johnson et al 2003, Kimmins et al 2004, cows (Kimmins et al 2004) and pigs (Garlow et al 2002), the bovine oviduct (Gabler et al 2003), and on the luminal surfaces of epithelial cells of human gastrointestinal and reproductive tracts, gall bladder, pancreas, lung, breast, urinary tract, salivary glands, and sweat glands (Brown et al 1992). OPN may be glycosylated, phosphorylated and sulfated, and its expression and post-translational modifications are tissue-specific and regulated by many hormones and growth factors (Denhardt & Guo 1993).…”
Section: Introductionmentioning
confidence: 99%